Efektivitas Pembelajaran Tilawati al-Qur’an di Madrasah Ibtidaiyah Negeri (MIN) Kota Blitar Jawa Timur - Nur Khasanah (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
The purpose of this research is First, to describe the implementation of recitation of the Qur'an at MIN Blitar City. Second, to analyze the effectiveness of learning tilawati al-Qur'an at MIN Blitar City. This type of research is qualitative with a case study approach. The research subjects were school principals, vice principals, Al-Qur'an teachers, and students. Data collection was carried out using in-depth interviews, documentation, and observation techniques. Data validity uses credibility, transferability, dependability, and confirmability techniques. The data were then analyzed in stages, namely data display, and data reduction. The research results show that; First, learning the tilawati Qur'an which is done offline every day before formal learning is carried out by integrating the schedule. Wisdom learning tilawati al-Qur'an is intended to improve the ability to read the Koran properly and correctly. For this reason, ustadzah al-Qur'an must have standard qualifications, including reading fluently and hafiz. Second, learning the Qur'an is carried out effectively.